DEVELOPING ENGLISH READING MATERIAL FOR FASHION DESIGN PROGRAM IN VOCATIONAL SCHOOL - Zhana Sabrina Amelia; Busmin Gurning; Isli Iriani Indiah Pane (Universitas Negeri Medan, 2017)
This study concern on how reading text materials are developed for fashion design vocational school. The objectives of this research were: (1) to design English reading material for students in Fashion Design Program, (2) to develop English reading material for students in Fashion Design Program. This study was conducted by using developmental research (R & D). The subject of the research was grade twelve in SMK N 10 Medan consisting of 33 students. Instrumentation for collecting data was document, questionnaire, and interview. After analyzing the data, the writer got the students’ need learning English based on their program in school. Based on the students’ need analysis, it was got some reading materials from the students’ book are not appropriate with the syllabus. Then, there is reading material that should develop based on their syllabus and their need. After the materials had been designed, the reading materials were done. The results show of the 84.1% from the Expert – lecturer and 92.1% from the Expert – English teacher, for the new reading material and the categorized is “relevant” as the reading material criteria. The developed teaching materials were related to the vocation that the students had; it was fashion design program. The development of materials followed six stages; those were gathering information and data, analyzing data, designing new reading material, validating expert, revising new reading material from experts’ suggestion and developing reading material (final product). Keywords: Develop, Reading Text Materials, Fashion Design, Vocational School, Developmental Research